2003
DOI: 10.2472/jsms.52.6appendix_154
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Diffusion Bonding of Superplastic Duplex Stainless Steel with Carbon Steel

Abstract: Solid state bonding between superplastic duplex stainless steel with carbon steel under low pressures is studied for the objectives to understand bonding behaviors and to determine mechanisms controlling bonding through the activation energy analysis. Experiments were carried out by combining several bonding parameters such as bonding temperatures, bonding pressures and surface roughness. Bond quality was evaluated by its tensile strength. Bonding strength increased with temperature, time and pressure but decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…To the authors' knowledge, this is the highest hardness value obtained through boronizing of ferrous alloys. As explained in the previous work (9) , through superplastic deformation of the DSS substrate's surface asperities, diffusion of boron atoms into the surface can be accelerated. The initial pressure applied not only superplastically deformed the surface asperities of substrate but also compacting the boron powder so that less void or space exists between them.…”
Section: Microstructure and Hardness Profile Of Spbmentioning
confidence: 84%
See 1 more Smart Citation
“…To the authors' knowledge, this is the highest hardness value obtained through boronizing of ferrous alloys. As explained in the previous work (9) , through superplastic deformation of the DSS substrate's surface asperities, diffusion of boron atoms into the surface can be accelerated. The initial pressure applied not only superplastically deformed the surface asperities of substrate but also compacting the boron powder so that less void or space exists between them.…”
Section: Microstructure and Hardness Profile Of Spbmentioning
confidence: 84%
“…The solution treated DSS was then cold-rolled to a plate through a reduction area of 75%. Figure 2 shows fine microstructure of the thermo-mechanically treated DSS after reheated at boronizing temperature of 1223 K. Under this temperature condition, superplastic elongation of 1050% has been achieved (9) . Specimens were cut from the thermo-mechanically treated plate to a dimension of 10 X 10 X 8 mm.…”
Section: Experimental Procedures 21 Substrate Materialsmentioning
confidence: 99%
“…Diffusion bonds of high-alloy austenitic steels are possible in a wide range of process parameters. Different authors report temperatures ranging from 850 to 1100 • C, contact pressures of 2 to 15 MPa and dwell times on temperature not exceeding 60 min [16][17][18]. However, for microstructured devices made from several layers, the experience of the authors showed that longer dwell times led to improved bonding results.…”
Section: Materials and Design Of Experimentsmentioning
confidence: 99%
“…Diffusion taking place on interface is important to consider the strength of SPF-DB. An example, in which diffusion affects the fracture strength of bonded materials by SPF-DB, is mentioned in this section [ 8 , 9 ].…”
Section: The Diffusion Of Carbon At Interface Of High Carbon Steelmentioning
confidence: 99%